LINGUACULTURAL FEATURES OF GODONYMS IN TASHKENT - D.A.Turdaliyeva (World Scientific Research Journal, 2025)
Abstract: This article explores the linguocultural characteristics of urban toponyms in Tashkent, Uzbekistan's capital. The naming of streets, districts, squares, and metro stations is analyzed through the lenses of semantics, etymology, and culture. The study reveals how these place names reflect the city's historical memory, national identity, ideological influences, and socio-cultural transformations. By examining selected examples, the paper underscores the importance of toponyms as more than just geographical markers but as carriers of linguistic and cultural significance.